2020
DOI: 10.1136/bmjopen-2019-032721
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and neonatal factors for the development of childhood visual impairment in primary and middle school students: a cross-sectional survey in Guangzhou, China

Abstract: ObjectivesIn this cross-sectional survey, we sought to determine the prevalence of and the influence of prenatal and neonatal factors on childhood visual impairment without correction (VIUC) in a paediatric population from Guangzhou, China.SettingThe health survey covered 11 administrative districts in Guangzhou, including 991 schools.ParticipantsAll of the primary and middle school students in Guangzhou were invited to complete an online questionnaire with the help of their parents. The results of physical ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
1
5
1
Order By: Relevance
“…Although most studies show a positive relationship between outdoor time and vision, our data revealed no such association [9,12,13].…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Although most studies show a positive relationship between outdoor time and vision, our data revealed no such association [9,12,13].…”
Section: Discussioncontrasting
confidence: 96%
“…Similar to our results, a very extensive study by Chong et al [17] revealed a reduced risk of myopia development in breastfed children (43% lower than nonbreastfed). Liu et al [24] had similar findings and demonstrated that children breastfed for a duration of more than six months had a 49.8% lower chance of developing myopia and that parental myopia was strongly associated with the child developing myopia, which was also highlighted in our results [12,13,24,25].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Study designs included cross-over trial, non-randomized interventions, and longitudinal with up to 4 years follow-up, and cross-sectional. Risks (injury)/harms were assessed objectively through eye examinations for myopia, visual acuity, and visual impairment; and subjectively pain/discomfort (abdominal, ankles/feet, back, elbow, hip/thigh, knee, lower back, lower limbs, neck and shoulder, neck, shoulder, upper back, upper limbs, wrist/hands, and overall pain or discomfort using the Nordic Musculoskeletal Questionnaire, HBSC survey, or study-specific questionnaires), headaches (study-specific questionnaires), well-being (self-report HBSC), and global health (parent-report questionnaire) a Intervention first condition, and control group first condition were in the same classroom b Only one study, with a small sample size c Unfavourable for odds of elbow, low back, neck, and shoulder pain, as well as for less neck pain, but null for all other areas of pain [ 98 ] d 2/3 studies had intervention and control groups in the same school e Study did not demonstrate psychometric testing of subjectively measured exposure variables f Only one study, but did have large sample size g 9/15 studies did not demonstrate psychometric testing of subjectively measured exposure variables h 5: null and unfavourable [1: unfavourable for too much homework and shoulder pain, but null for not enough and shoulder pain, and all neck pain [ 105 ]; 1: unfavourable for too much, null for not enough [ 106 ]; 1: unfavourable for > = 60 min and myopia, null for all visual acuity and myopia 1–30 and 31–60 min homework [ 107 ]; 1: unfavourable overall and > = 2 h of homework, null for 0.5–1.9 h/day [ 99 ]; 1: unfavourable for boys weekday homework and odds of pain, but null for all other outcomes and sub-groups (11/12 associations) [ 108 ]; 2 : favourable and null and unfavourable findings [1: dose response-generally favourable associations at 1–2 h of studying, unfavourable at > 3 h and 2–3 h [ 109 ]; 1: dose response-favourable associations at 6–8 and 8–10 h, but null for > 10 h and 4–6 h (compared to < 4 h), and unfavourable for extra learning tasks after class [ 110 ]]…”
Section: Resultsmentioning
confidence: 99%
“…h 5: null and unfavourable [1: unfavourable for too much homework and shoulder pain, but null for not enough and shoulder pain, and all neck pain [ 105 ]; 1: unfavourable for too much, null for not enough [ 106 ]; 1: unfavourable for > = 60 min and myopia, null for all visual acuity and myopia 1–30 and 31–60 min homework [ 107 ]; 1: unfavourable overall and > = 2 h of homework, null for 0.5–1.9 h/day [ 99 ]; 1: unfavourable for boys weekday homework and odds of pain, but null for all other outcomes and sub-groups (11/12 associations) [ 108 ]; 2 : favourable and null and unfavourable findings [1: dose response-generally favourable associations at 1–2 h of studying, unfavourable at > 3 h and 2–3 h [ 109 ]; 1: dose response-favourable associations at 6–8 and 8–10 h, but null for > 10 h and 4–6 h (compared to < 4 h), and unfavourable for extra learning tasks after class [ 110 ]]…”
Section: Resultsmentioning
confidence: 99%